P‐2.6: Research on Desensitization Medical Therapy Based on Virtual Reality. (24th February 2021) - Zhang, Qichang; wang, Lijun; Lv, Shitao
Abstract : As the pace of society gradually speeding up, more and more people came the problem of psychological fear. The traditional drug therapy trauma on the human body is very serious. The communication with the psychologist does not fully understand the patient's own situation, and it is easy to cause trauma to the psychologist. Virtual reality exposure therapy has important implications for the management of posttraumatic stress disorder and severe phobias that are difficult to treat with conventional psychotherapy and drugs. Based on the above situation, this paper proposes a psychological phobia detection scheme in a virtual environment based on EEG signals. The program began with a scene of virtual reality stimulation, EEG acquisition, combined with neural network algorithm, patient diagnosis and treatment. Experiments show that virtual reality‐based desensitization therapy has a better diagnosis and treatment effect on patients' fear.